Getting in touch with the company & interview techniques. Part 4 : RSM CDC case writing training material. - Yue, Tao, active 2024; Nolan, Jacqueline (London : Rotterdam School of Management, Erasmus University, 2024)
Effective communication and preparation are vital when reaching out to a company for case research. This involves sharing your case plan, specifying information needs, and setting clear boundaries. Interview techniques play a crucial role in gathering valuable insights, including principles of active listening and managing the interview process. Common pitfalls to avoid are discussed, such as asking double-barrelled questions and not acknowledging gaps in understanding. Finally, the importance of concluding interviews with clear next steps and follow-ups is emphasized for successful case development.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Interviewing -- Technique -- Case studies; Case method -- Case studies